Orthogonal Optimization Research on Various Nozzles of High-Speed Centrifugal Spinning - Zhang, Zhiming; Liu, Kang; Li, Wenhui; Ji, Qiaoling; Xu, Qiao; Lai, Zilong; Ke, Changjin (Frontiers in Bioengineering and Biotechnology, 2022)
High-speed centrifugal spinning is a burgeoning method of fabricating nanofibers by use of centrifugal force field. This paper studied four different spinning nozzles which were called stepped nozzle, conical-straight nozzle, conical nozzle, and curved-tube nozzle to explore the optimal nozzle structure for fabricating nanofibers. According to the principle of centrifugal spinning, the spinning solution flow states within the four nozzles were analyzed and the solution outlet velocity model was established. Then, the structural parameters of the four kinds of nozzles were optimized with the spinning solution outlet velocity as the test index by combining orthogonal test and numerical simulation. Based on the orthogonal test results, the influence of nozzle structure parameters on the solution outlet velocity was analyzed and the best combination of parameters of the centrifugal spinning nozzle structure was obtained. Subsequently, the four kinds of nozzles were used to fabricate nanofibers in laboratory, under different solution concentration, motor rotation speed and outlet diameters. Finally, the Scanning Electron Microscope (SEM) was applied to observe the morphology and surface quality of nanofibers. It was found that the surface of nanofibers manufactured by conical-straight nozzle and curved-tube nozzle was smoother than stepped and conical nozzles and the fiber diameter by conical-straight nozzle was minimal, followed by curved-tube nozzles, stepped, and conical nozzles in the diameter distribution of nanofibers.